Sunshine in Korea - Levin, Norman D.; Han, Yong-Sup (RAND Corporation, 2023)
The debate in South Korea over the government's engagement policy toward North Korea (the "sunshine" policy) did not start with Pyongyang's recent admission that it has been secretly pursuing a nuclear weapons program in violation of multiple international commitments. However, the evolution of the debate will be an important determinant of how the South Korean and broader international response to this latest North Korean challenge ultimately ends. This book provides a framework for viewing South Korean responses to this challenge, examining the South Korean debate over policies toward the North, analyzing the sources of controversy, and assessing their implications.